Laparoscopic colorectal resection: short-term outcomes after 60 procedures – A single center initial experience - Ćeranić, Miljan S.; Latinčić, Stojan M.; Skrobić, Ognjan M.; Gunjić, Dragan D.; Vasiljević, Jovica V.; Pavlov, Maja J. (Vojnosanitetski pregled, 2021)
Background/Aim. Laparoscopic colorectal surgery is now widely accepted surgical method in the treatment of malignant and benign colorectal diseases. It is getting constantly more supporters due to its positive effects on enhanced patient recovery. The aim of this study was to determine the safety of minimally invasive approach as well as perioperative data, oncologic results and postoperative data. Methods. Prospective observational cohort clinical study was carried out at the Department for Colorectal and Pelvic Oncologic Surgery, First Surgical University Hospital, Clinical Center of Serbia, Belgrade. We analyzed demographics records concerning the type of surgery, clinicopathological features and oncological data for all operated patients. Records on early postoperative follow-up were also evaluated. Results. Laparoscopic colorectal resection was performed in 60 patients. Mean age of patients was 65 (29–87) years. Majority of patients were man, 37 (62%) of them. The most common indication was colorectal cancer (43 patients, 71.6%); 12 (20%) patients were operated due to the colorectal polyps unfitted for colonoscopic resection and 5 (8.3%) were operated due to Crohn’s disease. Average number of lymph node harvested in patients with colorectal carcinoma was 22.5 (6–52). We achieved negative resection margins in all patients operated due to carcinoma. Mean duration of hospital stay was 5 (4–12) days. Postoperative complications were encountered in 5 (8.3%) patients. Overall mortality rate was 1.7% (1 patient died due to thromboembolism). Conclusion. This study showed that initiation of laparoscopic colorectal resection is feasible and safe with short hospital stay, adequate oncologic resection and number of lymph node harvested.